1997
DOI: 10.1073/pnas.94.23.12717
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phospholipase D by lysophosphatidylethanolamine, a lipid-derived senescence retardant

Abstract: Phospholipid signaling mediated by lipidderived second messengers or biologically active lipids is still new and is not well established in plants. We recently have found that lysophosphatidylethanolamine (LPE), a naturally occurring lipid, retards senescence of leaves, f lowers, and postharvest fruits. Phospholipase D (PLD) has been suggested as a key enzyme in mediating the degradation of membrane phospholipids during the early stages of plant senescence. Here we report that LPE inhibited the activity of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 45 publications
3
95
1
Order By: Relevance
“…1 and 2). All NAEs were effective inhibitors at high concentrations (200 m), similar to the concentrations reported for LPE (Ryu et al, 1997). In general, the long-chain, unsaturated NAEs demonstrated less inhibitory effects on castor bean PLD␣ than did saturated or shorter chain types (Fig.…”
Section: Nae and Pld␣ Activitysupporting
confidence: 51%
See 4 more Smart Citations
“…1 and 2). All NAEs were effective inhibitors at high concentrations (200 m), similar to the concentrations reported for LPE (Ryu et al, 1997). In general, the long-chain, unsaturated NAEs demonstrated less inhibitory effects on castor bean PLD␣ than did saturated or shorter chain types (Fig.…”
Section: Nae and Pld␣ Activitysupporting
confidence: 51%
“…In separate control experiments, exogenous myristic acid up to 10 m did not influence the activity of the cabbage or the castor bean PLD␣ (data not shown). Other workers have demonstrated that ethanolamine itself has no inhibitory effect on PLD (Ryu et al, 1997), suggesting that the inhibitory effect of NAE is conferred by a structural specificity of the entire molecule, and may be an inherent property of plant PLD␣ isoforms.…”
Section: Nae and Pld␣ Activitymentioning
confidence: 99%
See 3 more Smart Citations